Endoscopic Endonasal Skull Base Surgery: Advantages, Limitations, and Our Techniques to Overcome Cerebrospinal Fluid Leakage: Technical Note - ISHII, Yudo (Neurol Med Chir (Tokyo), 2014)
In recent years, resections of midline skull base tumors have been conducted using endoscopic endonasal skull base (EESB) approaches. Nevertheless, many surgeons reported that cerebrospinal fluid (CSF) leakage is still a major complication of these approaches. Here, we report the results of our 42 EESB surgeries and discuss the advantages and limits of this approach for resecting various types of tumors, and also report our technique to overcome CSF leakage. All 42 cases involved midline skull base tumors resected using the EESB technique. Dural incisions were closed using nasoseptal flaps and fascia patch inlay sutures. Total removal of the tumor was accomplished in seven pituitary adenomas (33.3%), five craniopharyngiomas (62.5%), five tuberculum sellae meningiomas (83.3%), three clival chordomas (100%), and one suprasellar ependymoma. Residual regions included the cavernous sinus, the outside of the intracranial part of the internal carotid artery, the lower lateral part of the posterior clivus, and the posterior pituitary stalk. Overall incidence of CSF leakage was 7.1%. Even though the versatility of the approach is limited, EESB surgery has many advantages compared to the transcranial approach for managing mid-line skull base lesions. To avoid CSF leakage, surgeons should have skills and techniques for complete closure, including use of the nasoseptal flap and fascia patch inlay techniques.